AN ANDROID DIGITAL MODERNIZATION ON BRASTAGI ULP CENTRALIZED METER RECORDING SERVICES - Ikardius Barus; Hamdani; Siti Anisah (Sean Institute, 2022)
Modernization is essential for technology, including electricity billing procedures, so PLN applies two systems, namely the prepaid system and the postpaid system. So this requires PLN to record customer meter data to each customer's house in an efficient way so that a system is needed to record customer meter data and can send it directly to a server called the Centralized Meter Record Application (ACMT) with a system that has been now integrated with AP2T and can be accessed online. This application is designed to be used on the android platform. This ACMT system, will be able to speed up the distribution of meter record data to the server. It can make it easier to evaluate and correct customer meter data.